2023
DOI: 10.1097/qad.0000000000003549
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with survival in patients with lymphoma and HIV

Abstract: Objective:To analyze the factors associated with survival in the largest cohort of individuals with HIV and lymphoma so far described in Brazil.Design:A retrospective, observational, multicenter study involving five institutions in São Paulo, Brazil.Methods:The medical records of consecutive patients with HIV diagnosed with lymphoma between January 2000 and December 2019 were screened. Inclusion criteria consisted of age over 17 years and a biopsy-confirmed diagnosis of lymphoma. The data collected included ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Despite the age of antiretroviral therapy (ART), which has greatly extended the life expectancy for people with HIV, HIV continue to be associated with an increased risk of death among patients with lymphoma [18,19]. Previous research has shown decreased survival for HIV-associated Burkitt lymphoma; however, these regional studies consisted of relatively small cohorts of patients (n < 300) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the age of antiretroviral therapy (ART), which has greatly extended the life expectancy for people with HIV, HIV continue to be associated with an increased risk of death among patients with lymphoma [18,19]. Previous research has shown decreased survival for HIV-associated Burkitt lymphoma; however, these regional studies consisted of relatively small cohorts of patients (n < 300) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer, particularly lymphoma, is the leading cause of death in people living with human immunodeficiency virus (HIV) in the combined antiretroviral therapy (cART) era [1][2][3]. During the first 6 months of cART use, individuals with HIV are at an increased risk of developing Hodgkin/non-Hodgkin lymphoma (HL/NHL), probably due to immune reconstitution inflammatory syndrome (IRIS), previously described in cases of opportunistic infections and Kaposi sarcoma [1,2,4]. The hallmark of IRIS is paradoxical worsening of an existing infection/disease or the appearance of a new condition shortly after initiating cART, together with a viral load drop ≥1 log and a concomitant increase in CD4 count [5].…”
Section: Introductionmentioning
confidence: 99%